Absenteísmo-doença entre servidores públicos municipais de Goiânia - Leão, Ana Lucia de Melo (2012)
Background: Sickness absence (SA), known as work disability justified by sick leave, can be an indicator of workers health status. In municipal government, like the rest of the country, the prevalence of SA and its main causes are still poorly documented, and are restricted to the analysis of some occupational groups, especially those who engage in health care or in institutions education. Estimates of the magnitude of SA vary widely and socio-demographic aspects related to nature and working conditions are among the main factors associated with the frequency and duration. Aims: To study the prevalence and the factors related to SA workers from the public sector in the municipality of Goiânia. Methods: Cross-sectional population-based study assessing prevalence and factors associated with sick leave lasting longer than three days for the health treatment from 2005 to 2010, in civil servants. Outcomes: 40.578 sick leave were assessed among 14.484 absent workers which generated 944.722 absent days. The indicators of sickness absence in that period were: prevalence of sick leave of 39.0%, higher among education professionals (47.7%) and health (41.9%), the mean duration of SA was 40 days / year per worker away and the average duration of Licenses was 23 days per episode. Predominance of female sexual workers, aged between 41 and 50 years, married, white, with high educational background, earning up to three minimal salaries, with their own house, with from 3 to 10 years of public service, having a professional bond and basically in operational tasks registered in the Municipal Secretariat of Education and Health. The main cause of sickness was mental and behavioral disorder followed by musculoskeletal diseases. The Multivariate analysis showed an association between sickness absence and the female subjects (OR 1,54 IC95%1,41-1,68), being older (OR 1,86 IC95% 1,48-2,32), married (OR 1,51 IC95% 1,13-2,02), having elementary school degree (OR 12,35 IC95% 10,39-14,69), income of up to three minimal salaries (OR 1,37 IC95% 1,21-1,55), having more working experience concerning the time(OR 3,39 IC95% 2,50-4,59), being professional in the health and educational area (OR 2,96 IC95% 2,60-3,38 and OR 2,90 IC95% 2,51- 3,36), as well as being part of the staff in the Municipal Secretariat of Education and Health (OR 1,69 IC95% 1,30-2,21 e OR 1,60 IC95% 1,23-2,09 ). Conclusions: The indicators of SA express the magnitude of this phenomenon in public service and can assist in the planning of health worker prioritizing the most vulnerable occupational groups whose socio-demographic characteristics and work organization influence on absenteeism due to illness.